The Training and Role of Young Doctoral Teachers in the Practice Education of Entrepreneurship and Innovation in Colleges and Universities - Wang, Peng; Qu, Xiaoya; Li, Na; Sun, Jinfeng (Transactions on Social Science, Education and Humanities Research, 2024)
In view of the serious shortage of teachers in the current innovation and entrepreneurship practice education in local colleges and universities in China, this paper conducted an experimental exploration on how to train young doctoral teachers in the innovation and entrepreneurship practice education in colleges and universities and how to play an important role in the process of innovation and entrepreneurship practice education. This paper analyzes the characteristics of new young doctoral teachers in colleges and universities, summarizes the common problems existing in the training of teachers, puts forward specific measures and practices for the training of young doctoral teachers, and carries out practice.